2015
DOI: 10.1523/jneurosci.0476-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Trans-Modulation of the Somatostatin Type 2A Receptor Trafficking by Insulin-Regulated Aminopeptidase Decreases Limbic Seizures

Abstract: Within the hippocampus, the major somatostatin (SRIF) receptor subtype, the sst2A receptor, is localized at postsynaptic sites of the principal neurons where it modulates neuronal activity. Following agonist exposure, this receptor rapidly internalizes and recycles slowly through the trans-Golgi network. In epilepsy, a high and chronic release of somatostatin occurs, which provokes, in both rat and human tissue, a decrease in the density of this inhibitory receptor at the cell surface. The insulin-regulated am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 66 publications
2
20
0
Order By: Relevance
“…Assuming that SST 2 signals in intracellular organelles, this could explain, at least in part, the long-lasting actions of SRIF analogs such as octreotide. Of note, although ECE-1 might be present in the hippocampus ( Barnes et al, 1997 ), the kinetics of SST 2 recycling were the same after activation by SRIF-14 or octreotide in hippocampal neurons ( De Bundel et al, 2015 ), suggesting that the ECE-1 role on SST 2 recycling is dependent upon cell types. Filamin A (FLNA), a scaffolding protein involved in intracellular trafficking of several transmembrane proteins ( Onoprishvili et al, 2003 ; Noam et al, 2014 ), has been shown to interact with the SST 2 in melanoma and pancreatic cell lines ( Najib et al, 2012 ).…”
Section: Somatostatin Receptormentioning
confidence: 99%
See 3 more Smart Citations
“…Assuming that SST 2 signals in intracellular organelles, this could explain, at least in part, the long-lasting actions of SRIF analogs such as octreotide. Of note, although ECE-1 might be present in the hippocampus ( Barnes et al, 1997 ), the kinetics of SST 2 recycling were the same after activation by SRIF-14 or octreotide in hippocampal neurons ( De Bundel et al, 2015 ), suggesting that the ECE-1 role on SST 2 recycling is dependent upon cell types. Filamin A (FLNA), a scaffolding protein involved in intracellular trafficking of several transmembrane proteins ( Onoprishvili et al, 2003 ; Noam et al, 2014 ), has been shown to interact with the SST 2 in melanoma and pancreatic cell lines ( Najib et al, 2012 ).…”
Section: Somatostatin Receptormentioning
confidence: 99%
“…Collectively, these studies highlight that SRIF released under physiologic or pathophysiological conditions regulates localization and trafficking of SST 2 consistent with results obtained in cell lines ( Csaba and Dournaud, 2001 ; Tulipano and Schulz, 2007 ; Jacobs and Schulz, 2008 ; Treppiedi et al, 2017 ). In hippocampal neuronal cells, SST 2 trafficking was analyzed in detail at different times after acute intracerebral octreotide injections or in primary neuronal culture exposed to SRIF ligands ( Csaba et al, 2001 , 2007 ; Lelouvier et al, 2008 ; De Bundel et al, 2015 ). These experiments demonstrated for the first time that GPCR cargoes recycle through the trans-Golgi network (TGN) after endocytosis.…”
Section: Somatostatin Receptormentioning
confidence: 99%
See 2 more Smart Citations
“…In the basal state, newly synthesized IRAP is targeted to the trans-Golgi network (TGN), evidenced by colocalization with a TGN-specific marker (TGN38) ( De Bundel et al, 2015 ). It is subsequently transported for storage to specialized endosomal vesicles in the perinuclear region of the cell, with slow recycling of these endosomes to the plasma membrane ( Figure 2 ; Shi et al, 2008 ; Jordens et al, 2010 ).…”
Section: Recognising the N-terminal Domain Of Irapmentioning
confidence: 99%